Root zone microbial communities of Artemisia ordosica Krasch. at different successional stages in Mu US Sandy Land: a metagenomic perspective with culturomics insights - Zhu, Wen; Han, Shuo; Cheng, Yao; Yu, Zhihong; Zhao, Guozhu; He, Xiangwei (Frontiers in Microbiology, 2025)
Phytoremediation offers a promising strategy for addressing the global challenge of land desertification. In the Mu Us Sandy Land of China, Artemisia ordosica Krasch. has emerged as a key species for desertification control. Its root-associated microbial communities may enhance the plant’s adaptability to sandy, nutrient-poor environments. Despite their ecological significance, comprehensive investigations of these microbial communities remain limited. In this study, microbial communities in the root zone (i.e., rhizosphere soil, non-rhizosphere soil, and root endosphere) of A. ordosica were analyzed via high-throughput sequencing and different isolation approaches across successional stages (moving dunes, semi-fixed dunes, and fixed dunes) in the Mu Us Sandy Land of northern China. Metagenomic analysis revealed that microbial diversity was significantly higher in the rhizosphere and non-rhizosphere soils than in the root endosphere; moving dunes exhibited lower diversity than semi-fixed and fixed dunes. Meanwhile, distinct microbial community structures across successional stages were revealed by principal coordinates analysis (PCoA), demonstrating substantial differences between the root endosphere and other zones. Environmental factors, including nitrate nitrogen (NO3−-N), organic matter (OM), available potassium (AK), and total potassium (TK), significantly influenced microbial community composition. Moreover, dominant genera such as Arthrobacter and Paraphoma were identified, potentially contributing to A. ordosica growth. From a culturomics perspective, 93 bacterial isolates were obtained using conventional streak plate and colony pick methods, with Firmicutes (37.63%) and Bacillus (23.66%) identified as the dominant taxa. In parallel, 14 fungal strains were isolated, primarily belonging to Penicillium (35.71%) and Aspergillus (21.43%), both of which are well-documented for their stress tolerance in arid ecosystems. A high-throughput cultivation and identification method, tailored to recover rare and slow-growing bacteria, was employed and successfully broadened the cultured diversity to include Proteobacteria (46.43%) and representatives of the rarely cultivated Deinococcus-Thermus phylum. This study provides metagenomic with culturomics insights into the microbial communities associated with A. ordosica, enhancing the understanding of plant–microbe interactions in sandy land ecosystems.